Managing Fisheries Conflicts in Southeast Asia - Lee, Wen Chiat; Viswanathan, K. Kuperan (2017)
Objective: This paper focuses on fisheries conflicts in Southeast Asia (ASEAN).Methodology: This paper draws on few cases in ASEAN and explores ways for reducing conflicts and managing fisheries sustainability in the region.Results: The community-based management approach is seen as a promising approach for reducing fisheries conflicts and improving fisheries as a whole. Implication: The institutional and technical requirements for implementing the approach is discussed in the paper.